Comparison of characteristics and antioxidant activities of sesame protein hydrolysates and their fractions - Rodjana Noptana; David Julian McClements; Lynne A. McLandsborough; Ekasit Onsaard (Heliyon, 2024)
Sesame meal is a by-product obtained from oil extraction. We investigated the characteristics and antioxidant activities of a sesame protein hydrolysate (SPH–B), as well as its peptide fractions. Four peptide fractions (F1; >100 kDa, F2; 10–100 kDa, F3; 1–10 kDa, and F4; <1 kDa) of SPH-B were prepared. The characteristics and antioxidant properties of SPH-B and its peptide fractions were evaluated. Sesame protein (SP) contained protein fractions with molecular weights ranging from 10 to 44 kDa, whereas SPH-B had peptide fractions ranging from 8 to 44 kDa. The peptide fractions had molecular weight ranging from 7 to 10 kDa. The four peptide fractions had a higher α-helix content and lower surface hydrophobicity than SPH-B and SP. They exhibited better antioxidant properties, with higher ABTS and DPPH radical scavenging activities, higher metal chelating activity, and greater inhibition of linoleic acid peroxidation, suggesting that sesame peptide fractions can use as plant-based functional ingredients and potentially health-promoting properties.